The Impact of Green Attitude and Green Self-Efficacy on Employee Green Intention: A Gender Comparative Study - Sumbul Waqas; Muhammad Arshad; Khush Bakhat Umer; Dr. Ehsan Iftikhar (Indus Journal of Social Sciences, 2025)
This study investigates the influence of employees’ green attitudes and green self-efficacy on their green behavioural intentions, grounded in the Theory of Planned Behavior (TPB). Using survey data collected from 495 employees in healthcare organizations across Pakistan, we examine an integrated model that not only tests direct effects but also explores gender as a moderating variable. Regression analysis performed via SPSS. These findings provide partial support for the hypothesized model, suggesting the need for further exploration of contextual or cultural variables influencing green workplace behaviours. Implications for organizational sustainability efforts and gender-responsive policy development are discussed.